A high belite ferrite cement and a method for producing the same
Patent Information
- Application Number
- CN202610539181.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-22
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-04-22
AI Technical Summary
[0002]高贝利特铁铝酸盐水泥以贝利特相和铁铝酸盐相为主要矿物组成,兼具早期强度发展快、后期强度持续增长、水化热低、耐腐蚀性优良等技术优势,在低温施工、快速修补、海工工程、大体积混凝土等领域具有良好应用前景,然而,该体系水泥熟料水化速率较快,初凝时间普遍较短,部分研究及工程应用表明其初凝时间可短至20-30分钟,现场可操作时间有限,难以满足大体积混凝土连续浇筑、复杂结构成型及长距离运输等施工工况要求,易因凝结过快造成混凝土工作性损失过快等质量缺陷
[0025]1、本发明通过复合矿化剂与复合增效剂的协同作用,有效优化了高贝利特铁铝酸盐水泥的凝结特性,在避免凝结过快的同时保障了水泥各龄期力学性能的提升,本发明制备的水泥初凝时间稳定在34-36min、终凝时间46-50min,有效延长了现场施工可操作时间,解决了传统该类水泥初凝短至20-30min导致的工作性损失快、施工质量缺陷等问题;且水泥28d抗压强度81.7-86.4MPa,克服了传统外掺缓凝剂易造成的强度大幅下降、力学性能波动的弊端。
Smart Images

Figure SMS_19 
Figure SMS_20
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminoferrite cement technology, specifically to a high-belite aluminoferrite cement and its preparation method. Background Technology
[0002] High belite aluminate-ferroferroaluminate cement is composed mainly of belite and aluminate-ferroferroaluminate phases. It has technical advantages such as rapid early strength development, continuous strength growth in the later stage, low heat of hydration, and excellent corrosion resistance. It has good application prospects in low-temperature construction, rapid repair, marine engineering, and large-volume concrete. However, the cement clinker in this system has a fast hydration rate and generally short initial setting time. Some studies and engineering applications show that its initial setting time can be as short as 20-30 minutes. The on-site workable time is limited, making it difficult to meet the requirements of continuous pouring of large-volume concrete, forming of complex structures, and long-distance transportation. It is also prone to quality defects such as rapid loss of concrete workability due to excessively rapid setting.
[0003] Currently, in industrial production and on-site construction, admixtures such as citric acid, tartaric acid, and boric acid are commonly used to adjust the setting time of cement in order to extend the construction operation time. However, the above-mentioned retarding components generally have problems such as high dosage sensitivity and poor compatibility. If the dosage is too low, it is difficult to achieve the ideal retarding effect and cannot meet the construction requirements. If the dosage is too high, it will inhibit the cement hydration process, which will lead to a significant decrease in the early strength and later strength of concrete, and at the same time, it will damage the key performance indicators such as cement mechanical properties and corrosion resistance.
[0004] Based on this, the present invention designs a high belite aluminate cement and its preparation method to solve the above problems. Summary of the Invention
[0005] In view of the above-mentioned shortcomings of the existing technology, the present invention provides a high belite aluminate cement and its preparation method.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for preparing high belite aluminate ferroaluminate cement includes the following steps:
[0008] S1: Weigh 76-88 parts by weight of calcium raw material, 22-30 parts by weight of silicon raw material, 15-20 parts by weight of aluminum raw material, 13-18 parts by weight of iron raw material, and 0.8-2.5 parts by weight of compound mineralizer;
[0009] S2: The raw material of S1 is ground and sieved through a roller press to homogenize it into a uniform raw material;
[0010] S3: The homogenized raw material is fed into a rotary kiln and calcined at 1310-1360℃. It is then cooled to 1020-1050℃ and then cooled to below 100℃ to obtain clinker.
[0011] S4: Weigh 78-86 parts clinker, 0.3-1.2 parts composite synergist, 12-15 parts gypsum, and 6-12 parts mixed materials by weight, then grind and sieve them through a roller press to obtain high belite aluminate cement.
[0012] Furthermore, the preparation method of the composite mineralizer is as follows:
[0013] A1. Weigh out sodium fluorosilicate, ammonium dihydrogen phosphate, and magnesium oxide in a molar ratio of 1:0.4-0.8:0.3-0.7;
[0014] A2. Add sodium fluorosilicate and ammonium dihydrogen phosphate to deionized water, and stir at 120-180 r / min at 35-55℃ until completely dissolved to prepare a composite mother liquor with a solid content of 15-25%.
[0015] A3. Magnesium oxide is fed into the reactor, and composite mother liquor is added at a rate of 1.2-3.5 parts / min. The mixture is kept at 40-60℃ and stirred at 200-300r / min for 60-120min to obtain the composite material. The composite material is then dried at 50-80℃ for 2-4h.
[0016] A4. The dried composite material from A3 is fed into a vibratory mill and ground for 15-30 minutes at a vibration frequency of 20-30Hz and a grinding media filling rate of 60-75%. After grinding, it is sieved to obtain the composite mineralizer.
[0017] Furthermore, the siliceous raw material is quartz sand and fly ash in a mass ratio of 1.5-2.7:2.2-3.4.
[0018] Furthermore, the iron raw material is iron tailings and sulfuric acid slag in a mass ratio of 2.5-3.8:2.9-4.6.
[0019] Furthermore, S2 specifically involves grinding the raw material from S1 using a roller press until 4-8% residue remains on a 0.08mm square hole sieve. The raw material is then fed into a continuous pneumatic homogenization chamber and homogenized for 35-50 minutes under a homogenization pressure of 0.12-0.18MPa to obtain a uniform raw material.
[0020] Furthermore, S3 specifically involves feeding homogenized raw materials into a rotary kiln and calcining them at 1310-1360℃ for 50-80 minutes. The materials are then fed into a grate cooler, where they are first cooled to 1020-1050℃ at a rate of 80-120℃ / h, and then cooled to below 100℃ at a rate of 30-50℃ / h to obtain clinker.
[0021] Furthermore, the composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid, and sodium borate in a molar ratio of 1:0.4-0.8:0.3-0.7.
[0022] Furthermore, the composite material is composed of metakaolin and quartz powder in a mass ratio of 1.5-2.4:1.8-3.1.
[0023] A high-belite aluminate cement prepared according to the method described above.
[0024] Compared with the prior art, the beneficial effects of this invention are as follows:
[0025] 1. This invention effectively optimizes the setting characteristics of high belite aluminoferrite cement through the synergistic effect of composite mineralizer and composite synergist. While avoiding excessively rapid setting, it ensures the improvement of mechanical properties of cement at all ages. The cement prepared by this invention has a stable initial setting time of 34-36 min and a final setting time of 46-50 min, which effectively extends the workable time for on-site construction and solves the problems of rapid workability loss and construction quality defects caused by the short initial setting time of traditional cements of this type (only 20-30 min). Moreover, the 28-day compressive strength of the cement is 81.7-86.4 MPa, overcoming the drawbacks of significant strength reduction and mechanical property fluctuation caused by traditional external admixtures of retarders.
[0026] 2. The formulation and preparation process of this invention significantly improve the acid and alkali corrosion resistance of high belite aluminate cement. The cement prepared by this invention has a mass loss rate of only 1.45-1.82% after 60 days of acid corrosion and a mass loss rate of 2.46-2.91% after alkali corrosion. The flexural strength retention rate under acid and alkali corrosion is over 95%, and the compressive strength retention rate is over 92%. This indicates that the component design of this invention enables the cement to have excellent durability in corrosive environments such as marine engineering, expanding its large-scale application scenarios in major projects. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0028] Example 1: This example provides a method for preparing high-belite aluminoferrite cement, including the following steps:
[0029] S1: Weigh 76 parts by weight of calcareous raw material (limestone), 22 parts by weight of siliceous raw material (quartz sand and fly ash in a mass ratio of 1.5:2.2), 15 parts by weight of aluminous raw material (bauxite), 13 parts by weight of ferrous raw material (iron tailings and sulfuric acid slag in a mass ratio of 2.5:2.9), and 0.8 parts by weight of composite mineralizer.
[0030] The preparation method of the composite mineralizer is as follows:
[0031] A1. Weigh out sodium fluorosilicate, ammonium dihydrogen phosphate, and magnesium oxide in a molar ratio of 1:0.4:0.3;
[0032] A2. Add sodium fluorosilicate and ammonium dihydrogen phosphate to deionized water, stir at 120 r / min at 35℃ until completely dissolved, and prepare a composite mother liquor with a solid content of 15%.
[0033] A3. Magnesium oxide is fed into the reactor, and composite mother liquor is added at a rate of 1.2 parts / min. The mixture is kept at 40℃ and stirred at 200 r / min for 60 min to obtain the composite material. The composite material is then dried at 50℃ for 2 h.
[0034] A4. The dried composite material from A3 is fed into a vibratory mill and ground for 15 minutes at a vibration frequency of 20 Hz and a grinding media filling rate of 60%. After grinding, it is passed through a 0.08 mm square hole sieve, and the sieve residue is controlled to be ≤3% to obtain the composite mineralizer.
[0035] S2: The raw material of S1 is ground by a roller press until 4-8% residue is left on a 0.08mm square hole sieve. Then it is fed into a continuous pneumatic homogenization chamber and homogenized for 35 minutes under a homogenization pressure of 0.12MPa to obtain a uniform raw material.
[0036] S3: The homogenized raw material is fed into a rotary kiln and calcined at 1310℃ for 50 minutes. Then it is sent to a grate cooler and cooled to 1020℃ at a rate of 80℃ / h, and then cooled to below 100℃ at a rate of 30℃ / h to obtain clinker.
[0037] S4: Weigh 78 parts clinker, 0.3 parts composite synergist, 12 parts gypsum, and 6 parts blended materials by weight, and then grind them through a roller press until 2-6% residue is left on a 0.08mm square hole sieve to obtain cement; send the ground cement into the finished product homogenization silo and pneumatically homogenize it under a pressure of 0.10MPa for 30 minutes to obtain high belite aluminoferrite cement.
[0038] The composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid and sodium borate in a molar ratio of 1:0.4:0.3;
[0039] The composite material is composed of metakaolin and quartz powder in a mass ratio of 1.5:1.8.
[0040] Example 2: This example provides a method for preparing high-belite aluminate-ferroaluminate cement, including the following steps:
[0041] S1: Weigh 88 parts by weight of calcareous raw material (limestone), 30 parts by weight of siliceous raw material (quartz sand and fly ash in a mass ratio of 2.7:3.4), 20 parts by weight of aluminous raw material (bauxite), 18 parts by weight of ferrous raw material (iron tailings and sulfuric acid slag in a mass ratio of 3.8:4.6), and 2.5 parts by weight of composite mineralizer.
[0042] The preparation method of the composite mineralizer is as follows:
[0043] A1. Weigh out sodium fluorosilicate, ammonium dihydrogen phosphate, and magnesium oxide in a molar ratio of 1:0.8:0.7;
[0044] A2. Add sodium fluorosilicate and ammonium dihydrogen phosphate to deionized water, stir at 180 r / min at 55℃ until completely dissolved, and prepare a composite mother liquor with a solid content of 25%.
[0045] A3. Magnesium oxide is fed into the reactor, and composite mother liquor is added at a rate of 3.5 parts / min. The mixture is kept at 60℃ and stirred at 300r / min for 120min to obtain the composite material. The composite material is then dried at 80℃ for 4h.
[0046] A4. The dried composite material of A3 is fed into a vibratory mill and ground for 30 minutes at a vibration frequency of 30Hz and a grinding media filling rate of 75%. After grinding, it is passed through a 0.08mm square hole sieve, and the sieve residue is controlled to be ≤3% to obtain the composite mineralizer.
[0047] S2: The raw material of S1 is ground by a roller press until 4-8% residue is left on a 0.08mm square hole sieve. Then it is fed into a continuous pneumatic homogenization chamber and homogenized for 50 minutes under a homogenization pressure of 0.18MPa to obtain a uniform raw material.
[0048] S3: The homogenized raw material is fed into a rotary kiln and calcined at 1360℃ for 80 minutes. Then it is sent to a grate cooler and cooled to 1050℃ at a rate of 120℃ / h, and then cooled to below 100℃ at a rate of 50℃ / h to obtain clinker.
[0049] S4: Weigh 86 parts clinker, 1.2 parts composite synergist, 15 parts gypsum, and 12 parts blended materials by weight, and then grind them through a roller press until 2-6% residue is left on a 0.08mm square hole sieve to obtain cement; send the ground cement into the finished product homogenization silo and pneumatically homogenize it under a pressure of 0.16MPa for 45 minutes to obtain high belite aluminoferrite cement.
[0050] The composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid and sodium borate in a molar ratio of 1:0.8:0.7;
[0051] The composite material is composed of metakaolin and quartz powder in a mass ratio of 2.4:3.1.
[0052] Example 3: This example provides a method for preparing high-belite aluminoferrite cement, including the following steps:
[0053] S1: Weigh out 82 parts by weight of calcareous raw material (limestone), 27 parts by weight of siliceous raw material (quartz sand and fly ash in a mass ratio of 2.1:2.7), 17 parts by weight of aluminous raw material (bauxite), 16 parts by weight of ferrous raw material (iron tailings and sulfuric acid slag in a mass ratio of 3.2:3.7), and 1.6 parts by weight of composite mineralizer.
[0054] The preparation method of the composite mineralizer is as follows:
[0055] A1. Weigh out sodium fluorosilicate, ammonium dihydrogen phosphate, and magnesium oxide in a molar ratio of 1:0.6:0.5;
[0056] A2. Add sodium fluorosilicate and ammonium dihydrogen phosphate to deionized water, stir at 160 r / min at 48℃ until completely dissolved, and prepare a composite mother liquor with a solid content of 20%.
[0057] A3. Magnesium oxide is fed into the reactor, and composite mother liquor is added at a rate of 2.4 parts / min. The mixture is kept at 53℃ and stirred at 260 r / min for 78 min to obtain the composite material. The composite material is then dried at 72℃ for 2 h.
[0058] A4. The dried composite material of A3 is fed into a vibratory mill and ground for 24 minutes at a vibration frequency of 30Hz and a grinding media filling rate of 65%. After grinding, it is passed through a 0.08mm square hole sieve, and the sieve residue is controlled to be ≤3% to obtain the composite mineralizer.
[0059] S2: The raw material of S1 is ground by a roller press until 4-8% residue is left on a 0.08mm square hole sieve. Then it is fed into a continuous pneumatic homogenization chamber and homogenized for 44 minutes under a homogenization pressure of 0.12MPa to obtain a uniform raw material.
[0060] S3: The homogenized raw material is fed into a rotary kiln and calcined at 1345℃ for 72 minutes. Then it is sent to a grate cooler and cooled to 1030℃ at a rate of 95℃ / h, and then cooled to below 100℃ at a rate of 46℃ / h to obtain clinker.
[0061] S4: Weigh 84 parts clinker, 0.7 parts composite synergist, 14 parts gypsum, and 8 parts blended materials by weight, and then grind them through a roller press until 2-6% residue is left on a 0.08mm square hole sieve to obtain cement; send the ground cement into the finished product homogenization silo and pneumatically homogenize it under a pressure of 0.16MPa for 38 minutes to obtain high belite aluminoferrite cement.
[0062] The composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid and sodium borate in a molar ratio of 1:0.6:0.5;
[0063] The composite material is composed of metakaolin and quartz powder in a mass ratio of 2.1:2.6.
[0064] Comparative Example 1: The difference between this comparative example and Example 3 is that the composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid and sodium borate in a molar ratio of 0.3:1.4:0.1.
[0065] Comparative Example 2: The difference between this comparative example and Example 3 is that sodium fluorosilicate was not added during the preparation of the composite mineralizer.
[0066] Comparative Example 3: The difference between this comparative example and Example 3 is that the composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid and sodium borate in a molar ratio of 0.3:1.4:0.1; sodium fluorosilicate was not added during the preparation of the composite mineralizer.
[0067] Experimental Example 1: The setting time (min) of the high belite aluminate ferroaluminate cement prepared by the present invention was tested according to GB / T 1346-2024.
[0068] Experimental Example 2: The compressive strength and flexural strength (MPa) of the high belite aluminate cement prepared according to the present invention were tested at 24h, 3d and 28d according to GB / T 17671-2021.
[0069] Experiment Example 3: Acid Corrosion Performance Testing;
[0070] Take the specimen after the test in Experiment Example 2 is completed and weigh its initial mass. Test the initial flexural strength Compressive strength ;
[0071] Prepare a sulfuric acid corrosion solution with a mass fraction of 5±0.1%, completely immerse the specimen in the corrosion solution, and ensure that the volume ratio of the corrosion solution to the total volume of the specimen is ≥20:1. Control the corrosion environment temperature at 20±2℃, use a sealed container, replace the corrosion solution with a fresh one every 7 days, and continue corrosion for 60 days.
[0072] After the corrosion cycle is completed, the specimen is removed and rinsed with running deionized water until no corrosion products remain. It is then placed in a well-ventilated environment at room temperature and allowed to air dry for 24 hours. The mass of the specimen after corrosion is then measured. Test the flexural strength after corrosion. , ;
[0073] The calculation formula is as follows:
[0074] ;
[0075] ;
[0076] .
[0077] Experiment Example 4: Alkali Corrosion Performance Test;
[0078] Take the specimen after the test in Experiment Example 2 is completed and weigh its initial mass. Test the initial flexural strength Compressive strength ;
[0079] Prepare a sodium hydroxide corrosion solution with a mass fraction of 10±0.1%, completely immerse the specimen in the corrosion solution, and ensure that the volume ratio of the corrosion solution to the total volume of the specimen is ≥20:1. Control the corrosion environment temperature at 20±2℃, use a sealed container, replace the corrosion solution with a fresh one every 7 days, and continue corrosion for 60 days.
[0080] After the corrosion cycle is completed, the specimen is removed and rinsed with running deionized water until no corrosion products remain. It is then placed in a well-ventilated environment at room temperature and allowed to air dry for 24 hours. The mass of the specimen after corrosion is then measured. Test the flexural strength after corrosion. Compressive strength ;
[0081] The calculation formula is as follows:
[0082] ;
[0083] ;
[0084] .
[0085] The results are shown in Table 1-2;
[0086] Table 1:
[0087]
[0088] As shown in the table above, the initial setting time of Examples 1-3 is 34-36 minutes and the final setting time is 46-50 minutes. The overall setting time is moderate and is longer than that of the comparative examples to varying degrees. Among them, the setting speed of Comparative Example 3 is the fastest, with an initial setting time of only 22 minutes and a final setting time of 31 minutes, which is much shorter than that of the Examples. This shows that the formula and preparation process of the present invention can effectively optimize the setting characteristics of cement and avoid setting too quickly.
[0089] The 24-hour compressive strength of the examples was between 57.8 and 61.2 MPa, and the flexural strength was between 7.1 and 7.7 MPa. The strength at this age of Comparative Examples 1 and 2 was slightly lower than that of the examples, while that of Comparative Example 3 was significantly lower, with a compressive strength of only 45.6 MPa and a flexural strength of only 5.1 MPa. The difference was significant, indicating that the ratio design of the composite mineralizer and composite synergist of the present invention can ensure the early strength of cement.
[0090] The 3-day compressive strength of the examples was 68.9-73.5 MPa, and the flexural strength was 8.5-9.1 MPa. The 3-day strength of comparative examples 1 and 2 was slightly lower than that of the examples. The 3-day compressive strength of comparative example 3 was only 55.2 MPa and the flexural strength was only 5.3 MPa. This further reflects that the formulation adjustment of the comparative examples will significantly inhibit the growth of cement mid-term strength, while the technical solution of the present invention can maintain a steady increase in mid-term strength.
[0091] The 28-day compressive strength of the examples was 81.7-86.4 MPa, and the flexural strength was 10.0-10.7 MPa, showing good ability to continuously increase strength in the later stage. The 28-day strength of Comparative Examples 1 and 2 was significantly lower than that of the examples. The 28-day compressive strength of Comparative Example 3 was only 67.3 MPa and the flexural strength was only 6.4 MPa, showing poor strength growth in the later stage. This shows that the formulation of the present invention can ensure the long-term mechanical properties of cement.
[0092] Table 2:
[0093]
[0094] As shown in the table above, the acid corrosion mass loss rates of Examples 1-3 were all within the range of 1.45-1.82%, with flexural strength retention rates all above 95% and compressive strength retention rates also above 92%. Overall, the mass loss under acid corrosion was small, mechanical properties were well preserved, and acid corrosion resistance was excellent. In contrast, the acid corrosion mass loss rates of Comparative Examples 1 and 2 increased significantly to 4.36%-4.71%, more than twice that of the Examples, while the flexural and compressive strength retention rates dropped to around 90%, indicating a significant deterioration in corrosion resistance. The acid corrosion mass loss rate of Comparative Example 3 reached 9.74%, more than five times that of the Examples, with a strength retention rate of only around 80%.
[0095] The alkali corrosion mass loss rate of Examples 1-3 was between 2.46% and 2.91%, the flexural strength retention rate was over 95%, and the compressive strength retention rate was over 92%. The alkali corrosion mass loss rate of Comparative Examples 1 and 2 increased to 4.29-4.58%, and the strength retention rate dropped to about 90%, indicating a decrease in alkali corrosion resistance. The alkali corrosion mass loss rate of Comparative Example 3 reached 8.27%, and the strength retention rate was only about 80%.
[0096] In summary, Comparative Example 1, which only adjusted the ratio of the composite synergist, and Comparative Example 2, which only removed sodium fluorosilicate from the composite mineralizer, showed similar degrees of deterioration in corrosion resistance. However, Comparative Example 3, which had both of the above-mentioned formulation deviations, showed a significant decrease in corrosion resistance, with all indicators being the worst among all samples. This indicates that the ratio of the composite mineralizer and the molar ratio of the composite synergist are both key to ensuring the corrosion resistance of cement, and the synergistic effect of the two components is of great significance in improving the corrosion resistance of cement.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing high-belite aluminate-ferroferrocement cement, characterized in that, Includes the following steps: S1: Weigh 76-88 parts by weight of calcium raw material, 22-30 parts by weight of silicon raw material, 15-20 parts by weight of aluminum raw material, 13-18 parts by weight of iron raw material, and 0.8-2.5 parts by weight of composite mineralizer; S2: The raw material of S1 is ground and sieved through a roller press to homogenize it into a uniform raw material; S3: The homogenized raw material is fed into a rotary kiln and calcined at 1310-1360℃. It is then cooled to 1020-1050℃ and then cooled to below 100℃ to obtain clinker. S4: Weigh 78-86 parts clinker, 0.3-1.2 parts composite synergist, 12-15 parts gypsum, and 6-12 parts blended materials by weight, then grind and sieve them through a roller press to obtain high belite aluminoferrite cement. The preparation method of the composite mineralizer is as follows: A1. Weigh out sodium fluorosilicate, ammonium dihydrogen phosphate, and magnesium oxide in a molar ratio of 1:0.4-0.8:0.3-0.7; A2. Add sodium fluorosilicate and ammonium dihydrogen phosphate to deionized water, and stir at 120-180 r / min at 35-55℃ until completely dissolved to prepare a composite mother liquor with a solid content of 15-25%. A3. Magnesium oxide is fed into the reactor, and composite mother liquor is added at a rate of 1.2-3.5 parts / min. The mixture is kept at 40-60℃ and stirred at 200-300r / min for 60-120min to obtain the composite material. The composite material is then dried at 50-80℃ for 2-4h. A4. The dried composite material of A3 is fed into a vibratory mill and ground for 15-30 minutes at a vibration frequency of 20-30Hz and a grinding media filling rate of 60-75%. After grinding, it is sieved to obtain the composite mineralizer. The composite synergist is composed of dihydroxysuccinic acid, aminotrimethylenephosphonic acid, and sodium borate in a molar ratio of 1:0.4-0.8:0.3-0.
7.
2. The method for preparing high belite aluminate ferroaluminate cement according to claim 1, characterized in that, The siliceous raw materials are quartz sand and fly ash in a mass ratio of 1.5-2.7:2.2-3.
4.
3. The method for preparing high-belite aluminate-ferroferrocement cement according to claim 1, characterized in that, The iron raw materials are iron tailings and sulfuric acid slag in a mass ratio of 2.5-3.8:2.9-4.
6.
4. The method for preparing high belite aluminate ferroaluminate cement according to claim 1, characterized in that, S2 specifically involves grinding the raw material from S1 using a roller press until 4-8% residue remains on a 0.08mm square hole sieve. The raw material is then fed into a continuous pneumatic homogenization chamber and homogenized for 35-50 minutes under a homogenization pressure of 0.12-0.18MPa to obtain a uniform raw material.
5. The method for preparing high belite aluminate ferroaluminate cement according to claim 1, characterized in that, S3 specifically involves feeding homogenized raw materials into a rotary kiln and calcining them at 1310-1360℃ for 50-80 minutes. The materials are then fed into a grate cooler, where they are first cooled to 1020-1050℃ at a rate of 80-120℃ / h, and then cooled to below 100℃ at a rate of 30-50℃ / h to obtain clinker.
6. The method for preparing high belite aluminate cement according to claim 1, characterized in that, The composite material is composed of metakaolin and quartz powder in a mass ratio of 1.5-2.4:1.8-3.
1.
7. A high-belite aluminate cement prepared by the method according to any one of claims 1-6.
Citation Information
Patent Citations
High belite iron aluminate cement clinker and preparation method thereof
CN121573921A